Efficient Portofolio Composition of Indonesian Islamic Bank Financing - Nisful Laila (Entrepreneurship And Sustainability Center, 2019)
The purpose of this research is to determine the composition of an efficient portfolio in the financing of ten Islamic banks. The theory of efficient portfolio by Markowitz is a modern portfolio theory used for analyzing the combination of various investment instruments to form efficient portfolio points at efficient frontier lines. The efficient composition portfolio measurement of Islamic bank in this study uses return, standard deviation, variance-covariance, correlation coefficient, and variation coefficient of investment instruments between 2011 and 2015. This study uses quantitative research achieved using Microsoft Excel. The result of this research shows that the average composition of an efficient portfolio of each Islamic bank is as follows: 48.62% for Mudharabah-Musyarakah, 41.63% for Murabahah, 8.03% for Ijarah, and 8.31% for Istishna. It can be seen that Mudharabah-Musyarakah and Murabahah are more dominant than the other financing types.